Successful Posterior Canal Wall Reconstruction with Tissue-Engineered Cartilage. Issue 1 (February 2019) - Ito, Ken; Toma-Hirano, Makiko; Yasui, Takuya
Difficulties are associated with reconstruction of middle ear bony structures in surgery for destructive lesions, including cholesteatoma. Although autologous cartilage appears to be the optimal choice because of its resistance to infection, the harvesting of sufficient volumes may be challenging. Therefore, regenerative medicine techniques to obtain sufficient material for reconstruction are awaited. We herein present a case of middle ear surgery for cholesteatoma with a sufficient volume of stick-shaped tissue-engineered cartilage produced from a piece of autologous auricular cartilage and autologous serum, with sufficient firmness to reconstruct bony structures. During surgery, sections of tissue-engineered cartilage were placed side by side to reconstruct the posterior canal wall. The postoperative course was uneventful. This is the first-in-human report of reconstructing middle ear bony structures with tissue-engineered cartilage. The results suggest a promising future for the satisfactory reconstruction of middle ear structures with minimal morbidity at the donor site.